STEM Integration Training in Learning for Teachers of SMK Kesehatan Proskill Indonesia Pekanbaru and Tualang: Pelatihan Integrasi STEM dalam Pembelajaran untuk Guru SMK Kesehatan Proskill Indonesia Pekanbaru dan Tualang - Adolf Bastian; Sari, Ermina; Raudhah Awal; Martalasari; Sri Whayuni; Ennie Chahyadi (Universitas Lancang Kuning, 2025)
Science, Technology, Engineering and Mathematics (STEM) education is seen as a way to create quality and competitive human resources entering the Industrial Revolution 4.0 era of the 21st century. The Ministry of Education and Culture of the Republic of Indonesia initiated its own STEM education trend since 2018. However, the STEM education movement in Indonesia is still rare, so STEM education needs to be developed. This service activity is based on the partner's problem, namely that the science teachers at this vocational school do not really know about STEM education, and so far there has never been anything held regarding the introduction of STEM education and how to integrate STEM in lessons. This service activity is carried out through the introduction of STEM education and integrating STEM education in science lessons to improve teacher professionalism. As an evaluation material for the success of implementing this service, participants were given a pretest and post-test regarding the participants' understanding and insight regarding STEM and its integration in learning. Based on the results of the pretest and posttest that have been carried out, it can be concluded that the training activities succeeded in increasing the insight and skills in integrating STEM in learning among science teachers at Proskill Indonesia Health Vocational Schools in Pekanbaru and Tualang, namely by 82.81%. Based on the results of the satisfaction survey regarding the presentation of resource persons, implementation of activities, usefulness and sustainability of activities, they received a good response from training participants.